Targeted PLGA-Chitosan Nanoparticles for NIR-Triggered Phototherapy and Imaging of HER2-Positive Tumors - Polina A. Kotelnikova; Victoria O. Shipunova; Sergey M. Deyev (MDPI AG, 2023)
Targeted medicine uses the distinctive features of cancer cells to find and destroy tumors. We present human epidermal growth factor receptor 2 (HER2)-targeted PLGA-chitosan nanoparticles for cancer therapy and visualization. Loading with two near-infrared (NIR) dyes provides imaging in the NIR transparency window and phototherapy triggered by 808 nm light. Nile Blue (NB) is a biocompatible solvatochromic NIR dye that serves as an imaging agent. Laser irradiation of IR-780 dye leads to a temperature rise and the generation of reactive oxygen species (ROS). Resonance energy transfer between two dyes allows visualization of tumors in a wide range of visible and IR wavelengths. The combination of two NIR dyes enables the use of nanoparticles for diagnostics only or theranostics. Modification of poly(lactic-co-glycolic acid) (PLGA)-chitosan nanoparticles with trastuzumab provides an efficient nanoparticle uptake by tumor cells and promotes more than sixfold specificity towards HER2-positive cells, leading to a synergistic anticancer effect. We demonstrate optical imaging of the HER2-positive mouse mammary tumor and tumor-specific accumulation of PLGA-IR-780-NB nanoparticles in vivo after intravenous administration. We managed to achieve almost complete suppression of the proliferative activity of cells in vitro by irradiation with an 808 nm laser with a power of 0.27 W for 1 min at a concentration at which nanoparticles are nontoxic to cells in the dark.